Structure and expression of the murine L-myc gene. - Legouy, E (1987)
We have isolated a 12 kb clone from the murine genome which we show by DNA transfection studies to contain an entire functional L-myc gene and the transcriptional promoter sequences necessary for its expression. We have also isolated a 3.1 kb cDNA sequence from a murine brain cDNA library which corresponds to most of the L-myc mRNA. We have identified the L-myc coding region within the genomic clone by a combination of S1 nuclease analyses. Northern blotting analyses and comparative nucleotide sequence analyses with the cDNA clone. The L-myc gene appears to be organized similarly to the other well-characterized myc-family genes, c-myc and N-myc. The predicted amino acid coding sequence of the L-myc gene indicates that the L-myc protein is significantly smaller than c- and N-myc, but is highly related. In particular, comparison of the N- and c-myc protein sequences reveals seven relatively conserved regions interspersed among non-conserved regions; the L-myc gene retains five of these conserved regions but lacks two others. In addition, a portion of one highly conserved region is encoded within a different region of the L-myc gene but, due to changes in the size of L-myc exons relative to those of N- and c-myc, maintains its overall position in the peptide backbone with respect to other conserved regions. We discuss these findings in the context of potential functional domains and the possibility of overlapping and distinct activities of myc-family proteins.